effective system for detecting Iris yellow spot virus transmission by Thrips tabaci - Inoue, T; Murai, T; Natsuaki, T (Plant pathology, 2010)
A simple, effective and convenient laboratory leaf system was developed to detect transmission of Iris yellow spot virus (IYSV) by thrips. It was shown that IYSV was transmitted highly efficiently by adults and also by larvae of five thelytokous populations of Thripstabaci from distinct areas in Japan: over all these populations, transmission efficiency of adults ranged from 20·4% (19/93) to 41·1% (76/185) and that of larvae from 17·3% (14/81) to 44·1% (67/152). Finally, it was demonstrated that IYSV infection was not detrimental to the development and fecundity of thrips until early adulthood. Larval mortalities of virus-exposed thrips were higher than in their unexposed counterparts in all three populations, but the differences were not significant. The results demonstrated that T. tabaci populations have considerable potential to cause outbreaks of IYSV and spread the disease because of their efficient transmission of the virus.